2011
DOI: 10.1097/iae.0b013e3181f84fc1
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy and Internal Limiting Membrane Peeling With Perfluoropropane Tamponade or Balanced Saline Solution for Myopic Foveoschisis

Abstract: Vitrectomy with ILM peeling does not increase the risk of iatrogenic macular hole formation. The poor elasticity of the ILM and the traction of membranous structure on the surface of the ILM play important roles in the development of myopic foveoschisis. In eyes undergoing vitrectomy and ILM peeling for myopic foveoschisis, C3F8 tamponade results in more rapid anatomical resolution and greater improvement in BCVA than balanced saline solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 26 publications
1
20
2
3
Order By: Relevance
“…This contrasts somewhat with the observations in a previous report by Zheng et al 24 of the surgical outcomes of 20-gauge pars plana vitrectomy for MF. In their study C 3 F 8 tamponade resulted in more rapid anatomical resolution and a greater improvement in BCVA than balanced saline solution.…”
Section: Discussioncontrasting
confidence: 99%
“…This contrasts somewhat with the observations in a previous report by Zheng et al 24 of the surgical outcomes of 20-gauge pars plana vitrectomy for MF. In their study C 3 F 8 tamponade resulted in more rapid anatomical resolution and a greater improvement in BCVA than balanced saline solution.…”
Section: Discussioncontrasting
confidence: 99%
“…22,23 These results can be explained by the effects of gas tamponade on paravascular lamellar or full-thickness retinal breaks that led to the more rapid resolution of a myopic MR.…”
Section: Discussionmentioning
confidence: 88%
“…[20][21][22][23] Ultrastructural study 24 showed collagen fibers and cellular debris on the inner surface of excised ILM in eyes with myopic MR. However, the removal of the ILM may increase the incidence of postoperative complications, including the development of an MH and an MHRD.…”
mentioning
confidence: 99%
“…Dyes should be used for ILM removal in highly myopic eyes because the ILM is transparent and fragile in these cases. In recent studies, the dyes used for the peeling of ILM in foveoschisis were triamcinolone acetonide or indocyanine green [20,21,22], and not Brilliant Blue G. In fact, indocyanine green has recently been reported to have a potential retinal toxicity compared with Brilliant Peel in an experimental study [23]. In our opinion, Brilliant Blue G staining should be considered in all cases with myopic foveoschisis to make the surgery easy and effective, and can lead to anatomical success as we report.…”
Section: Discussionmentioning
confidence: 99%